2014
DOI: 10.1093/qjmed/hcu236
|View full text |Cite
|
Sign up to set email alerts
|

Acute tubulointerstitial nephritis in Scotland

Abstract: Incidence of biopsy-proven ATIN in Scotland has been rising over the past decade with the majority of cases drug induced. Evidence supporting corticosteroid treatment is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 11 publications
3
46
1
5
Order By: Relevance
“…There is conflicting evidence from retrospective series, with some studies suggesting a benefit for steroids, with faster and greater recovery of renal function [12, 22], whereas other studies have showed no benefit of steroid treatment [5, 7, 24]. The outcomes of recent published series are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is conflicting evidence from retrospective series, with some studies suggesting a benefit for steroids, with faster and greater recovery of renal function [12, 22], whereas other studies have showed no benefit of steroid treatment [5, 7, 24]. The outcomes of recent published series are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Valluri et al . [7] reported no significant difference in serum creatinine in steroid-treated and untreated patients with D-AIN. Steroid-treated patients had more severe AKI at the time of biopsy, suggesting greater improvement in renal function in these patients compared with those not treated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two trends can be observed from the serum creatinine data: first, patients in more recent studies had better renal function at baseline than patients in older studies; second, patients treated with corticosteroids had poorer renal function compared with those who did not receive corticosteroid therapy. More recent studies have attempted to report renal function before the onset of DI‐AIN …”
Section: Resultsmentioning
confidence: 99%
“…The need for RRT was reported in six studies; however, the time point reported for initiation varied across studies, including two studies where the time point was unclear. Two studies reported the need for RRT around the time of biopsy .…”
Section: Resultsmentioning
confidence: 99%